Impact of Teachers’ Commitment to the Relationship between Transformational Leadership and Sustainable Teaching Performance - Mohammed Alzoraiki, Mohammed Alzoraiki; Abd Rahman Ahmad, Abd Rahman Ahmad; Ali Ahmed Ateeq, Ali Ahmed Ateeq; Gehad Mohammed Ahmed Naji, Gehad Mohammed Ahmed Naji; Qais Almaamari, Qais Almaamari; Baligh Ali Hasan Beshr, Baligh Ali Hasan Beshr (mdpi, 2023)
: In the field of education, ongoing processes, and optimal schoolwork outcomes require educational leadership, especially in developing countries, due to the lack of sustainable teaching performance and effective leadership. The present study aims to examine the mediating role of teachers’ commitment to transformational leadership and sustainable teaching performance. The sample of the study was selected using a stratified random sampling technique. Out of the 450 copies distributed to the participants, only 374 were retrieved as valid. The hypotheses of the study were tested using PLS–SEM. The findings showed a positive effect of transformational leadership on teachers’ commitment. Moreover, transformational leadership was also found to positively impact teachers’ performance. In contrast, the teachers’ commitment was revealed to positively affect sustainable teaching performance. Finally, the study showed that the teachers’ commitment mediated the relationship between transformational leadership and sustainable teaching performance. This study is unique for being among the few studies that examine the effects of principals’ transformational leadership. It provides educational leaders and policymakers with significant insights by providing a roadmap that aids in understanding the most influential factors on teaching performance sustainability. Consequently, this study holds significant practical relevance for leaders in the field of education and policymakers, as they provide valuable insights into policies and practices that can be implemented to foster sustainability in the school environment.